2018
DOI: 10.1016/s1872-2067(18)63123-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensionally ordered macroporous SnO2-based solid solution catalysts for effective soot oxidation

Abstract: A series of three-dimensionally ordered macroporous (3DOM) SnO2-based catalysts modified by the cations Ce 4+ , Mn 3+ , and Cu 2+ have been prepared by using a colloidal crystal templating method and tested for soot combustion under loose contact condition. XRD and STEM mapping results confirm that all the secondary metal cations have entered the lattice matrix of tetragonal rutile SnO2 to form non-continuous solid solutions, thus impeding crystallization and improving the surface areas and pore volumes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The catalytic activity of a catalyst in soot combustion is not only related to the intrinsic performance of the catalyst [12], but also to the contact efficiency between the solid catalyst and soot particles [13][14][15]. In our previous works, we found that a three-dimensionally ordered macroporous (3DOM) structure with large uniform pores (>50 nm) is a good way to improve the contact efficiency between the soot and catalyst, and we demonstrated the superior catalytic performance of 3DOM-structured catalysts in soot combustion [16][17][18][19][20]. For deep oxidation, the redox property of the 3DOM oxides is crucial to enhance their catalytic activity in soot combustion, and this is related to the surface active sites, which involves oxygen vacancies or coordinatively unsaturated metal cations for O2 activation [21][22][23].…”
Section: Introductionmentioning
confidence: 93%
“…The catalytic activity of a catalyst in soot combustion is not only related to the intrinsic performance of the catalyst [12], but also to the contact efficiency between the solid catalyst and soot particles [13][14][15]. In our previous works, we found that a three-dimensionally ordered macroporous (3DOM) structure with large uniform pores (>50 nm) is a good way to improve the contact efficiency between the soot and catalyst, and we demonstrated the superior catalytic performance of 3DOM-structured catalysts in soot combustion [16][17][18][19][20]. For deep oxidation, the redox property of the 3DOM oxides is crucial to enhance their catalytic activity in soot combustion, and this is related to the surface active sites, which involves oxygen vacancies or coordinatively unsaturated metal cations for O2 activation [21][22][23].…”
Section: Introductionmentioning
confidence: 93%
“…46,47 In addition, the construction of 3DOM solid solution structure can also produce a large number of surface active oxygen sites, which are critical to improve the catalytic activity. 45 Particularly, for toluene deep oxidation, SnO 2 catalysts with stable and different surface areas were fabricated by our group recently. By enlarging the surface area, the quantities of both surface active oxygen and acidic sites can be linearly improved due to the formation of more lattice defects and surface Sn 4+ cations, hence upgrading the toluene combustion activity significantly.…”
Section: Introductionmentioning
confidence: 99%
“…It leads to the difficulties due to lack of contact between soot particles and active sites on the internal surface of catalysts. Using 3DOM materials which have macroporous structure (> 50 nm) can effectively increase the mass transfer efficiency and the number of available active sites [61][62][63]. Combining the benefits of the 3DOM structure and excellent reactive properties of perovskite materials could lead to promising catalytic performance.…”
Section: Soot Combustionmentioning
confidence: 99%